Peran Unit Pengelola Darah Rumah Sakit Terhadap Peningkatan Kinerja Layanan Transfusi Darah: Tinjauan Literatur Naratif - Marsaban, Adhika Putra; Nadjib, Mardiati (UI Scholars Hub, 2025)
The performance of hospital blood transfusion services is crucial for patient safety and overall operational effectiveness. Blood management, as a vital and limited resource, plays a significant role. Traditional centralized blood management models often face challenges regarding response speed, potential waste, and quality control. As an alternative, Unit Pengelola Darah Rumah Sakit (UPDRS) offers the potential for performance enhancement. This narrative literature review is based on 16 relevant scientific articles identified through a database search (Scopus, Proquest, Wiley, Google Scholar) and a selection process visualized with a PRISMA diagram. Key findings identified significant impacts on cost efficiency, time efficiency (faster Turnaround Time), blood utilization (waste reduction, improved C:T ratio), and service quality and safety. Overall, the role of UPDRS tends to be positive for performance enhancement, particularly in speed and utilization, but its impact is contextual and requires strong internal management and adequate investment. Implementation challenges such as initial costs and regulations need to be considered.